OSMR is a potential driver of inflammation in amyotrophic lateral sclerosis - Wenzhi Chen; Shishi Jiang; Shu Li; Cheng Li; Renshi Xu (Neural Regeneration Research, 2024)
Amyotrophic lateral sclerosis is a neurodegenerative disease, and the molecular mechanism underlying its pathology remains poorly understood. However, inflammation is known to play an important role in the development of this condition. To identify driver genes that affect the inflammatory response in amyotrophic lateral sclerosis, as well as potential treatment targets, it is crucial to analyze brain tissue samples from patients with both sporadic amyotrophic lateral sclerosis and C9orf72-related amyotrophic lateral sclerosis. Therefore, in this study we used a network-driven gene analysis tool, NetBID2.0, which is based on SJARACNe, a scalable algorithm for the reconstruction of accurate cellular networks, to experimentally analyze sequencing data from patients with sporadic amyotrophic lateral sclerosis. The results showed that the OSMR gene is pathogenic in amyotrophic lateral sclerosis and participates in the progression of amyotrophic lateral sclerosis by mediating the neuroinflammatory response. Furthermore, there were differences in OSMR activity and expression between patients with sporadic amyotrophic lateral sclerosis and those with C9orf72-related amyotrophic lateral sclerosis. These findings suggest that OSMR may be a diagnostic and prognostic marker for amyotrophic lateral sclerosis.